Nutritional Significance and Antioxidant-Mediated Antiaging Effects of Finger Millet: Molecular Insights and Prospects - Kumar, Anil; Rani, Madhu; Mani, Shalini; Shah, Pallavi; Singh, Dev Bukhsh; Kudapa, Himabindu; Varshney, Rajeev K. (Frontiers in Sustainable Food Systems, 2021)
Aging is a multifaceted process that is associated with progressive, lethal, and unalterable changes like damage to different molecules (DNA, proteins, and lipids), cells, tissues, and organs. It is an inevitable process but can be delayed by both genetic and dietary interventions. Besides aging, premature death and age-associated diseases can be dealt with diet regulation and the use of compounds that inhibit the stress responsiveness or promote the damage repair signaling pathways. Natural compounds offer a repertoire of highly diverse structural scaffolds that can offer hopeful candidate chemical entities with antiaging potential. One such source of natural compounds is millets, which are minor cereals with an abundance of high fiber, methionine, calcium, iron, polyphenols, and secondary metabolites, responsible for numerous potential health benefits. The present review article elucidates the nature and significance of different phytochemicals derived from millets with a major focus on finger millet and highlights all the important studies supporting their health benefits with special emphasis on the antiaging effect of these compounds. The present article also proposes the possible mechanisms through which millets can play a significant role in the suppression of aging processes and aging-related diseases by influencing genetic repair, protein glycation, and stress-responsive pathways. We further discuss well-established natural compounds for their use as antiaging drugs and recommend raising awareness for designing novel formulations/combinations from them so that their maximum antiaging potential can be harnessed for the benefit of mankind.